Pengaruh Produk Domestik Regional Bruto Sektor Pertanian dan Luas Panen Padi terhadap Penyerapan Tenaga Kerja Sektor Pertanian di Kabupaten Badung (Jurnal Agribisnis dan Agrowisata, 2025)
The Influence of Gross Regional Domestic Product in the Agricultural Sector and Rice Harvested Area on Agricultural Sector Employment in Badung Regency. The agricultural sector is one of the main fields driving national growth, as it plays an important role in the economy and in providing employment opportunities. Badung Regency, part of Bali Province, has an economy dominated by the tourism sector; however, agriculture still contributes to the regional economy. Although tourism is the main economic driver, the agricultural sector continues to play a significant role, particularly in providing local food supplies and employment opportunities for rural communities. This study aims to analyze the influence of the agricultural sector's Gross Regional Domestic Product (GRDP) and the harvested area of rice on labor absorption in the agricultural sector in Badung Regency, both partially and simultaneously. The data used in this study are secondary time-series data from 2005 to 2023 sourced from the Badung Regency Central Bureau of Statistics (BPS). The data were analyzed using a multiple linear regression model with the assistance of Eviews 12 software. The results of the study show that simultaneously, the agricultural sector’s Gross Regional Domestic Product (GRDP) and the harvested area of rice have a significant effect on labor absorption in the agricultural sector in Badung Regency. The coefficient of determination of the model in this study is 39.03%. This means that variations in the agricultural sector's Gross Regional Domestic Product (GRDP) and the harvested area of rice explain 39.03% of the variation in labor absorption in the agricultural sector in Badung Regency, while the remaining 60.97% is explained by other variables not included in the model. Partially, however, the agricultural sector's Gross Regional Domestic Product (GRDP) does not have a significant effect on labor absorption in the agricultural sector in Badung Regency. Based on the results, the government needs to develop policies to sustain the growth of the harvested area of rice and labor absorption.
Keywords: labor absorption; gross regional domestic product; rice harvested area